Bread-Making Quality and Reduction of Acrylamide Content Using Weissella confusa Strain V20 from Desert Plant Stipagrostis pungens as Sourdough Additive - Imene Fhoula; Islem Dammak; Insaf Nachi; Imen Smida; Mnasser Hassouna; Imene Hadda Ouzari (Fermentation)
The impact of wheat sourdough inoculated with a promising lactic acid bacterium Weissella confusa V20, isolated from a Tunisian desert plant, on the quality characteristics of sourdough and bread as well as on acrylamide formation was evaluated. W. confusa V20 sourdough (SWc) did not provide high final acidity and could effectively metabolize sucrose, resulting in significant (p < 0.05) increases in glucose (44.5%) and fructose (84.2%) levels. A substantial decrease (p < 0.05) in free asparagine was observed upon fermentation, reducing from 16 ± 0.9 mg/100 g dry weight (d.w.) in the control dough with baker’s yeast (DBB) to 9.9 ± 0.4 mg/100 g d.w. in the dough inoculated with W. confusa V20 sourdough (DWc) and to 14.2 ± 0.2 mg/100 g d.w. in the dough produced with spontaneous sourdough (DSS). To improve the texture and flavor of the bread, the sourdough process should be further optimized in a strain-specific approach. V20 sourdough was more effective in enhancing the quality of the dough and bread compared to sourdough fermented with yeast. W. confusa V20 proved to be highly effective in reducing acrylamide levels, achieving a significant 62% decrease compared to the control.